Probing the binding mechanism of the verbascoside and human serum albumin by fluorescence spectroscopy and molecular docking approach - Zheng, Shi-jie; Zheng, Na; Zhang, Meng-li; Wu, Fang-fang; Yang, Shu-de; Cheng, Xian-hao; Bao, Hai-ying; Zhang, Rui (Monatshefte für Chemie, 2023)
The interactional mechanism and conformational changes of the verbascoside–human serum albumin (VB–HSA) complex were rigorously examined via fluorescence spectroscopy (FS), synchronous FS (S-FS), three-dimensional (3D) FS, and molecular docking (MD). Based on our analysis, VB quenched the HSA intrinsic fluorescence via a combinatory static and dynamic quenching mechanism. The binding constant and quantity of binding sites were next calculated using the Scatchard equation. The thermodynamic variables revealed that the van der Waals forces and hydrogen bonding (H-bonding) were dominant interacting forces in the VB–HSA complex. Furthermore, using displacement examinations with site markers, we showed that VB interacted with HSA at site II (subdomain IIIA). Additionally, based on our S-FS and 3D FS analyses, VB and HSA binding altered the polarity and microenvironment surrounding the tyrosine residues. Lastly, the interaction between VB and HSA amino acid residues was further validated using MD. The binding sites of VB in HSA from the MD analysis and the competition experiment remained consistent. This experiment comprehensively reflected the interaction between VB and HSA via the quenching type, number of binding sites, binding constant, force type, binding distance, binding site, and VB effect on the conformation of HSA. Our conclusions provide a basis for the future examination of the transport mechanism and action mechanism of VB in vivo, which is of great significance for the in-depth understanding of the pharmacokinetics and pharmacodynamics of VB. Graphical abstract